Women Empowerment through Self -Help Groups in India – A Comprehensive Literature Review (Journal of Informatics Education and Research, 2024)
India is a developing country with high ratio of Rural Population and high Masculinity index. If we look into the History, it has been founded that Male have more authority and power compare to the Woman and this practice is still continue in some areas of the Country. Government is continuously focusing on the Development by promoting several schemes for it. SHG is the Scheme launched by National Rural Livelihood Mission which emphasise on the Development of Rural poor through the Empowerment of Women. In this Review Paper we have tried to study different results related to women Empowerment through Self-Help Group in India. Additionally, it has been tried to understand different definitions of SHG and its importance also. The Literature says that Self-help Group is a group which is working for betterment of its members in terms of Economic, Social, Educational and Political level. SHG bank Linkage Programme is important to include the rural and excluded people into the financial system. It can contribute to the total Savings of the country which ultimately increase the Lending rate and funds can be utilised for development purpose. So, the development of the country can be improved by reducing the unemployment and poverty in the Country.